Komitmen Iman Pelayan Khusus (Diaken dan Penatua) Terhadap Tugas Pelayanan di Jemaat GMIM SION Kuyanga Wilayah Tombatu Utara - Ngalo, Rinthia Reflany Golung (UPT Penelitian Fakultas Teologi Universitas Kristen Indonesia Tomohon, 2022)
When God created man in the world, God wanted man to live in obedience and loyalty to Him. The church exists to bear witness to the truth of God revealed through the sacrifice and work of Christ as the Savior of mankind. The church presents people who are allowed to become special ministers, namely deacons, elders, religious teachers, and pastors to carry out ministry work, namely preaching the gospel about Christ. The most important thing as a special servant is to have a faith commitment and keep it, than they can carry out services effectively and responsibly as well their services be conclude successful. The purpose of this study is to describe the understanding of elders and deacons who do not carry out their duties and responsibilities as a faith commitment because there are several factors that affect the effectiveness of their ministry.